ANALISIS PENGARUH PERKEMBANGAN FISIK, KOGNITIF, DAN PSIKOSOSIAL TERHADAP AKADEMIK PESERTA DIDIK DI SMK YAPALIS KRIAN - Antok Widodo; Eli Masnawati (CV. Denasya Smart Publisher, 2024)
Educational psychology is a basic knowledge that underlies the teaching profession. A teacher who has an understanding of educational psychology will be able to develop and use psychological principles better in teaching it. When learning activities are taking place, we often find students who are not focused when the teacher is delivering the material, are sleepy, or are busy themselves with small things they have made. If a teacher does not understand educational psychology, it will be a challenge for him later. The physical, cognitive and psychosocial development of middle and upper level students has a huge influence on their achievement, both academic and non-academic. At this level, students' exploration power is much broader and increases drastically than at the junior secondary level. For this reason, teachers' understanding of educational psychology is really needed in accompanying, directing and guiding their students to achieve their best achievements at school.